Avaliação para aprendizagem da educação física na educação infantil: 10 anos de produção acadêmica (2010-2020) - Xerente, Daniel Simnãkrã (Universidade Federal do Tocantins, 2023)
The present work, through a systematic review, has the bias to situate the broad understanding of a certain theme/subject that circumvent science in its particular group. The general objective of the research is to analyze academic productions that circumvent the area of Physical Education on assessment for learning in the context of early childhood education. The approached method was based on the systematic review, from the mapping of an indexer (DOAJ). In view of this, the analysis of the results allowed the perception of distinct movements that occurred during the scientific productions between the referred dates (2010-2020). The first movement was between 2010 and 2015, which had only one publication, showing little productivity and the second movement occurs between 2016 and 2020, we can observe that there was a stabilization followed by an increase in productions in studies on evaluation in early childhood education. It is also perceived, as gaps, the lack of dissemination in the North region about the evaluation of early childhood education and indigenous education. However, the analyzes reinforce the encouragement of science producers to conduct productions in the indicated contexts and highlight the need for studies that are linked to the characteristics of the pairing that advance the productions over the years.